Beyond Menopause - Navigating Holistic Approach in Managing Dry Eyes - Ashwini, B. N. (Asian Journal of Pharmaceutics (AJP), 2024)
Among all ocular conditions, dry eye remains one of the most prevalent in clinical practice, ranging from 5% to 50% with higher variations in signs than symptoms. Increased age, female sex, and Asian ethnicity are among the most consistent risk factors for developing dry eye disease. The prevalence of dry eye increased by 14.4% in people aged 48–91, with the prevalence of the disorder more than doubling after the age of 59. Females are more prone to develop dryness, especially in the post-menopausal age group. Sex hormones play a key role in maintaining the homeostasis of the tear film. Hence, older women tend to develop dry eyes more than the other age groups. Considering the clinical features of dry eyes and analyzing the diseases in Ayurveda Netra Roga, the disease closely resembles the condition Shushkakshipaka Dosha predominance according to Sushruta is vata and Vagbhata explains it as vata pitta pradhanavyadhi. Aggravation of vata and pitta dosha leads to the shoshana of nethragatasneha contributed by kapha dosha. Considering the age and ritunivrutii kala (menopausal age), both are dominated by vata and also the disease. In consideration with the normal dry eyes population, this age group needs special consideration in addressing both post-menopausal dry eyes and other menopause-related issues. Hence, this review is planned to establish the correlation between dry eyes and shushkakshipaka to explore a better alternative treatment for post-menopausal dry eyes, and improve overall health in this population.